PUBLIC OPINION ON THE PROVISION OF CRISIS INTERVENTION BY HELPING PROFESSIONS - Šrobárová, Soňa; Markovič, Daniel; Gazdík, Dávid (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
A crisis in a person's life is a state in which an individual encounters an obstacle in his or her life that he or she cannot overcome with standard solutions strategies. Simultaneously, a person must/have to start to solve the situation and not let the problem grow into a difficult situation. The crisis is generally perceived as a threat to the individual who finds himself in it. However, some authors mention the positive potential it can have. As this is a new situation in a person's life, it encourages him to think about the future and the changes that can get him out of a crisis. Crisis intervention is a professional service provided by social educators, social workers, or psychologists. The research aims to find out how the public perceives the issue of crisis intervention. What crises have the respondents already encountered, and what help they prefer. In addition, what is the public's knowledge of the basic concepts and forms of assistance provided? The sample size is 309 respondents. We investigated whether there was a significant difference in the characteristics of the crisis intervention concerning education, which we verified with the Chi-Square test and whether there is concerning age and the relationship between surviving the crisis and seeking professional help.